Investigation on the association between college students’ smartphone-related behaviors and sleep quality during COVID-19 - Qi Chen; Nur Syuhada binti Mat Sin; Afeez Nawfal bin Mohd Isa; Duobao Chen (PLoS ONE, 2025)
Objective This study examines the quantifiable effects of pre-sleep smartphone use on sleep quality among college students during the COVID-19 pandemic, aiming to identify high-risk behaviors and inform targeted interventions. Methods Based on data from 508 students of different genders and academic years, the study first conducted univariate and multivariate logistic regression analyses to explore the association between smartphone-related behaviors and sleep quality. Subsequently, the adjusted smartphone behaviors were stratified by gender(male/female) and academic year(freshmen/Sophomore/juniors) into subsets for further subgroup analysis, aiming to examine the relationship and impact of smartphone-related behaviors on sleep disturbancess across different genders and academic years. Results he analysis revealed that specific pre-sleep activities were significantly associated with sleep quality. Notably, playing games before sleep (OR=6.071, p<0.001), late-night phone use (OR=2.824, p=0.002), having the phone off during sleep (OR=3.311, p<0.001), and using social media apps (OR=2.797, p=0.005) were linked to an increased risk of sleep disturbancess. Conversely, video-watching (OR=0.349, p=0.007) and moderate music listening (OR=0.220, p=0.004) were associated with a reduced risk of sleep disturbancess. Further analysis indicated that behaviors such as playing games and having the phone off during sleep significantly increased the risk of sleep disturbancess across different genders and academic years (OR>1, p<0.05). Conclusion During the COVID-19 pandemic, smartphone-related behaviors such as having the phone off during sleep, playing games before sleep, and using social media apps were identified as risk factors affecting sleep quality. This study provides empirical evidence for developing interventions aimed at improving sleep quality among college students in the context of heightened stress and disrupted routines caused by the pandemic.